Silicon-carbon negative electrode slurry as well as preparation method and application thereof
By adjusting the order of adding the carboxymethylcellulose sodium solution and polyacrylic acid binder, the viscosity and equipment wear of the silicon carbon negative electrode slurry are reduced, and the volume expansion of CVD silicon carbon is suppressed, which solves the problems of high viscosity, serious equipment wear and poor dispersion in the preparation process of traditional slurry, and the battery performance of lithium-ion batteries is improved.
Patent Information
- Application Number
- CN202411993492.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
During the preparation of traditional negative electrode slurry, the viscosity is high, the equipment wears severely, and the dispersion and uniformity are poor, making it difficult to ensure the suppression of volume expansion of CVD silicon carbon during use.
By adjusting the order of adding the carboxymethylcellulose sodium solution and polyacrylic acid binder, the viscosity of the silicon carbon negative electrode slurry is reduced, the wear on the equipment is reduced, and the volume expansion of CVD silicon carbon is inhibited through the synergistic effect of the carboxymethylcellulose sodium solution and polyacrylic acid binder.
The viscosity, solid content and fineness of the slurry are all within the standard range, reducing equipment wear, inhibiting the volume expansion of CVD silicon carbon, and improving the battery performance of lithium-ion batteries.
Smart Images

Figure CN119786538A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries and relates to a silicon-carbon negative electrode slurry and a preparation method and application thereof. Background Art
[0002] The manufacturing process of lithium-ion battery pole pieces is an important part of the entire lithium-ion battery manufacturing process and has a significant impact on the performance of lithium-ion batteries. The negative electrode slurry is a non-Newtonian high-viscosity fluid formed by mixing the negative electrode active material, binder, solvent, thickener and other powders and liquids evenly. The fluid needs to have a certain viscosity, good fluidity and a sufficiently small particle size.
[0003] In the traditional negative electrode slurry preparation process, negative electrode active materials, conductive carbon, binders, and dispersants are often added together and stirred and mixed. However, this not only places high demands on the stirring equipment, but also accelerates the wear and aging of the equipment. Moreover, the prepared slurry cannot guarantee good dispersion and uniformity, and large particles will remain. At the same time, the viscosity and solid content of the slurry cannot meet the expected standards.
[0004] Especially when CVD silicon carbon is used as the negative electrode active material, since it is often accompanied by large volume changes during the charge and discharge process, a binder with stronger adhesion is required. However, the molecular weight and viscosity of such binders are usually large. It is difficult to obtain a negative electrode slurry with good dispersion and uniformity using traditional methods, and it will cause serious wear on the stirring equipment.
[0005] Therefore, how to develop a method for preparing negative electrode slurry that can effectively reduce the slurry viscosity during the stirring process, reduce the requirements for stirring equipment, and at the same time ensure that the negative electrode slurry has good dispersion and uniformity, so that CVD silicon carbon will not produce a large volume expansion during use, is an urgent problem to be solved. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a silicon-carbon negative electrode slurry and a preparation method and application thereof. The preparation method provided by the present invention effectively reduces the viscosity of the silicon-carbon negative electrode slurry during the preparation process through the specific order of adding sodium carboxymethyl cellulose solution and polyacrylic acid binder, reduces the wear on the equipment, and greatly reduces the requirements for the stirring equipment. It can ensure that the viscosity, solid content and fineness of the slurry are within the standard range, inhibit the volume expansion phenomenon of CVD silicon-carbon during use, and the preparation method is simple and suitable for large-scale application.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a silicon-carbon negative electrode slurry, the preparation method comprising:
[0009] (1) mixing sodium carboxymethyl cellulose powder and a solvent to obtain a sodium carboxymethyl cellulose solution;
[0010] (2) performing a second mixing of the negative electrode active material and the conductive agent to obtain active material powder;
[0011] (3) adding a portion of the sodium carboxymethyl cellulose solution, the first portion of the polyacrylic acid binder, and the solvent to the active substance powder for a third mixing to obtain an intermediate slurry;
[0012] (4) adding the second part of the polyacrylic acid binder to the intermediate slurry for a fourth mixing, and then adding the remaining sodium carboxymethyl cellulose solution, the third part of the polyacrylic acid binder and the solvent for a fifth mixing;
[0013] The negative electrode active material includes CVD silicon carbon.
[0014] It can be understood that CVD silicon carbon refers to a silicon-carbon composite material prepared by chemical vapor deposition (CVD).
[0015] In the present invention, by adjusting the order of adding sodium carboxymethyl cellulose solution and polyacrylic acid binder during the preparation of silicon-carbon negative electrode slurry, the viscosity of the silicon-carbon negative electrode slurry during the preparation is effectively reduced, the wear of the slurry mixing on the equipment is reduced, and the viscosity, solid content and fineness of the slurry can be ensured to be within the standard range; at the same time, thanks to the synergistic effect of sodium carboxymethyl cellulose solution and polyacrylic acid binder, the volume expansion phenomenon of CVD silicon-carbon during use is effectively suppressed, and the preparation method is simple and suitable for large-scale application.
[0016] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0017] Preferably, taking the total mass of the solid components in the silicon-carbon negative electrode slurry as 100%, in step (1), the mass proportion of the sodium carboxymethyl cellulose powder is 0.5-2%, for example, 0.5%, 0.8%, 1.0%, 1.3%, 1.5%, 1.8% or 2.0%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] In the present invention, by regulating the amount of sodium carboxymethyl cellulose added in the preparation of the negative electrode slurry, the mixing effect of the silicon-carbon negative electrode slurry can be further optimized, which is more conducive to improving the comprehensive performance of the slurry.
[0019] Preferably, in step (1), the mass ratio of the sodium carboxymethyl cellulose powder to the solvent is (1-2%):(98-99%), for example 1.0%:99.0%, 1.2%:98.8%, 1.4%:98.6%, 1.6%:98.4%, 1.8%:98.2%, 2.0%:98.0%, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0020] Preferably, the solvent comprises deionized water.
[0021] Preferably, the first mixing process is: a first stirring for 30 to 60 minutes at an orbital speed of 15 to 18 rpm and a dispersion speed of 500 to 1000 rpm, and then a second stirring for 300 to 500 minutes at an orbital speed of 20 to 30 rpm and a dispersion speed of 1000 to 2000 rpm.
[0022] For example, during the first stirring process of the first mixing, the revolution speed may be 15 rpm, 16 rpm, 17 rpm or 18 rpm, the dispersion speed may be 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm or 1000 rpm, and the stirring time may be 30 min, 40 min, 50 min or 60 min; during the second stirring process of the first mixing, the revolution speed may be 20 rpm, 21 rpm, 22 rpm, 23 rpm, 24 rpm, 25 rpm, 26 rpm, 27 rpm, 28 rpm, 29 rpm, 30 rpm, 31 rpm, 32 rpm, 33 rpm, 34 rpm, 35 rpm, 36 rpm, 37 rpm, 38 rpm, 39 rpm, 40 rpm, 41 rpm, 42 rpm, 43 rpm, 44 rpm, 45 rpm, 46 rpm, 47 rpm, 48 rpm, 49 rpm, 50 rpm, 51 rpm, 52 rpm, 53 rpm, 54 rpm, 55 rpm, 56 rpm, 57 rpm, 58 rpm, 59 rpm, The dispersion speed can be 1000rpm, 1100rpm, 1200rpm, 1300rpm, 1400rpm, 1500rpm, 1600rpm, 1700rpm, 1800rpm, 1900rpm or 2000rpm, etc., and the stirring time can be 300min, 350min, 400min, 450min or 500min, etc., but are not limited to the listed values, and other values not listed within the numerical range are equally applicable.
[0023] In the present invention, whether to use the second stirring can be selected according to the quality requirements of the slurry. After the first stirring, a relatively uniformly mixed sodium carboxymethyl cellulose solution can be obtained. By adding the second stirring, the mixing effect of the sodium carboxymethyl cellulose solution can be further improved.
[0024] Preferably, the viscosity of the sodium carboxymethyl cellulose solution is 10000-20000 mPa·s, for example 10000 mPa·s, 12000 mPa·s, 14000 mPa·s, 16000 mPa·s, 18000 mPa·s or 20000 mPa·s, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] Preferably, after the first stirring is completed, the pot wall and the stirring paddle are scraped, the vacuum is turned on, and the circulating water is turned on.
[0026] Preferably, the negative electrode active material further includes graphite.
[0027] Preferably, the mass ratio of the graphite, CVD silicon carbon and conductive agent is (88-96%):(3-10%):(1-2%), for example 88%:10%:2%, 90%:8%:2%, 92%:6%:2%, 94%:4%:2%, 96%:3%:1%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] Preferably, the second mixing process is: performing a third stirring for 30 to 60 minutes at a revolution speed of 15 to 25 rpm and a dispersion speed of 200 to 1000 rpm.
[0029] For example, during the second mixing process, the revolution speed can be 15rpm, 16rpm, 17rpm, 18rpm, 19rpm, 20rpm, 21rpm, 22rpm, 23rpm, 24rpm or 25rpm, etc., the dispersion speed can be 200rpm, 300rpm, 400rpm, 500rpm, 600rpm, 700rpm, 800rpm, 900rpm or 1000rpm, etc., and the stirring time can be 30min, 40min, 50min or 60min, etc., but are not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0030] Preferably, taking the total mass of the solid components in the silicon-carbon negative electrode slurry as 100%, the total mass of the first part, the second part and the third part of the polyacrylic acid binder accounts for 2 to 4%, for example, 2.0%, 2.5%, 3.0%, 3.5% or 4.0%, etc., but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0031] In the present invention, the amount of polyacrylic acid binder added can be selected according to the amount of CVD silicon carbon added. By adjusting the total amount of polyacrylic acid binder added during the preparation of silicon carbon negative electrode slurry, a better balance between reducing slurry viscosity and inhibiting CVD silicon volume expansion can be achieved.
[0032] Preferably, taking the total mass of the first part, the second part and the third part of the polyacrylic acid adhesive as 100%, the mass proportion of the first part of the polyacrylic acid adhesive in step (3) is 20-40%, for example, 20%, 25%, 30%, 35% or 40%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] Preferably, taking the mass of the sodium carboxymethyl cellulose solution in step (1) as 100%, the mass proportion of the partial sodium carboxymethyl cellulose solution in step (3) is 20-50%, for example, 20%, 25%, 30%, 35%, 40%, 45% or 50%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] In the present invention, by adjusting the amount of the polyacrylic acid binder and the sodium carboxymethyl cellulose solution added in step (3), the mixing effect of the silicon-carbon negative electrode slurry can be further optimized, which is more conducive to the uniform dispersion of the slurry.
[0035] Preferably, the third mixing process is: a fourth stirring for 10 to 30 minutes at an orbital speed of 10 to 15 rpm, and then a fifth stirring for 60 to 90 minutes at an orbital speed of 25 to 35 rpm and a dispersion speed of 2000 to 3500 rpm.
[0036] For example, in the fourth stirring process of the third mixing, the revolution speed can be 10rpm, 11rpm, 12rpm, 13rpm, 14rpm or 15rpm, and the stirring time can be 10min, 15min, 20min, 25min or 30min, etc.; in the fifth stirring process of the third mixing, the revolution speed can be 25rpm, 26rpm, 27rpm, 28rpm, 29rpm, 30rpm, 31rpm, 32rpm, 33rpm, 34rpm or 35rpm, etc., the dispersion speed can be 2000rpm, 2200rpm, 2400rpm, 2600rpm, 2800rpm, 3000rpm, 3200rpm or 3500rpm, etc., and the stirring time can be 60min, 65min, 70min, 75min, 80min, 85min or 90min, etc., but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0037] Preferably, taking the sum of the masses of the first part, the second part and the third part of the polyacrylic acid binder as 100%, in the fourth mixing of step (4), the mass proportion of the second part of the polyacrylic acid binder is 20-40%, for example, 20%, 25%, 30%, 35% or 40%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] In the present invention, the amount of the second part of the polyacrylic acid binder added can be adjusted according to the amount of the first part of the polyacrylic acid binder added to better reduce the viscosity of the slurry during stirring, reduce wear on equipment, and achieve better slurry mixing effect.
[0039] Preferably, the fourth mixing process is: a sixth stirring for 10 to 30 minutes at an orbital speed of 10 to 15 rpm and a dispersion speed of 200 to 500 rpm, and then a seventh stirring for 60 to 120 minutes at an orbital speed of 25 to 35 rpm and a dispersion speed of 2000 to 3500 rpm.
[0040] For example, in the sixth stirring process of the fourth mixing, the revolution speed can be 10rpm, 11rpm, 12rpm, 13rpm, 14rpm or 15rpm, the dispersion speed can be 200rpm, 250rpm, 300rpm, 350rpm, 400rpm, 450rpm or 500rpm, and the stirring time can be 10min, 15min, 20min, 25min or 30min, etc.; in the seventh stirring process of the fourth mixing, the revolution speed can be 25rpm, 26rpm, 27rpm, 28rpm, 29rpm, 30rpm, 31rpm, 32rpm, 33rpm, 34rpm, 35rpm, 36rpm, 37rpm, 38rpm, 39rpm, 40rpm, 41rpm, 42rpm, 43rpm, 44rpm, 45rpm, 46rpm, 47rpm, 48rpm, 49rpm, 50rpm, 51rpm, 52rpm, 53rpm, 54rpm, 55rpm, 56rpm, 57rpm, 58rpm, 59rpm, 60rpm, 61rpm, 62rpm, 63rpm, 64rpm, 65rpm, 66rpm, 67rpm, 68rpm, 69rpm, 70rpm, 71rpm, 72rpm, 73rpm, 74rpm, 75rpm, 76rpm, 77rpm, 78rpm, 79rpm, 80rpm, 81rpm, 82rpm, 83rpm, 84rpm, 85rpm, 86rpm, 87rpm The abovementioned values may be 9rpm, 30rpm, 31rpm, 32rpm, 33rpm, 34rpm or 35rpm, etc., the dispersion speed may be 2000rpm, 2200rpm, 2400rpm, 2600rpm, 2800rpm, 3000rpm, 3200rpm or 3500rpm, etc., the stirring time may be 60min, 70min, 80min, 90min, 100min, 110min or 120min, etc., but are not limited to the abovementioned values, and other values not listed within the abovementioned value range are equally applicable.
[0041] Preferably, the fifth mixing process of step (4) is: an eighth stirring for 10 to 30 minutes at an orbital speed of 10 to 15 rpm and a dispersion speed of 400 to 1000 rpm, and then a ninth stirring for 90 to 120 minutes at an orbital speed of 25 to 35 rpm and a dispersion speed of 2000 to 3500 rpm.
[0042] For example, in the eighth stirring process of the fifth mixing, the revolution speed can be 10rpm, 11rpm, 12rpm, 13rpm, 14rpm or 15rpm, etc., the dispersion speed can be 400rpm, 500rpm, 600rpm, 700rpm, 800rpm, 900rpm or 1000rpm, and the stirring time can be 10min, 15min, 20min, 25min or 30min, etc.; in the ninth stirring process of the fifth mixing, the revolution speed can be 25rpm, 26rpm, 27rpm, 28rpm, 29rpm, 30rpm, etc. The abovementioned values may be 9rpm, 30rpm, 31rpm, 32rpm, 33rpm, 34rpm or 35rpm, etc., the dispersion speed may be 2000rpm, 2200rpm, 2400rpm, 2600rpm, 2800rpm, 3000rpm, 3200rpm or 3500rpm, etc., the stirring time may be 90min, 95min, 100min, 105min, 110min, 115min or 120min, etc., but are not limited to the abovementioned values, and other values not listed within the abovementioned value range are equally applicable.
[0043] Preferably, the viscosity of the silicon-carbon negative electrode slurry is 3000-6000mPa·s, for example, 3000mPa·s, 3500mPa·s, 4000mPa·s, 4500mPa·s, 5000mPa·s, 5500mPa·s or 6000mPa·s, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] In the present invention, two stirring speeds are used in each mixing process of step (3) and step (4), which can further reduce the wear of the equipment by the solid particles in the slurry during the stirring process.
[0045] As a preferred technical solution, the preparation method comprises the following steps:
[0046] (1) Taking the total mass of the solid components of the silicon-carbon negative electrode slurry as 100%, weigh 0.5-2% of sodium carboxymethyl cellulose powder by mass, and prepare a sodium carboxymethyl cellulose solution according to the mass ratio of sodium carboxymethyl cellulose powder to solvent of (1-2%): (98-99%), and perform a first stirring for 30-60 minutes at a revolution speed of 15-18 rpm and a dispersion speed of 500-1000 rpm. After the first stirring is completed, scrape the pot wall and the stirring paddle, turn on the vacuum, turn on the circulating water, and perform a second stirring for 300-500 minutes at a revolution speed of 20-30 rpm and a dispersion speed of 1000-2000 rpm, so as to obtain a sodium carboxymethyl cellulose solution with a viscosity of 10000-20000 mPa·s;
[0047] (2) performing a third stirring for 30 to 60 minutes at a revolution speed of 15 to 25 rpm and a dispersion speed of 200 to 1000 rpm according to a mass ratio of graphite, CVD silicon carbon powder and conductive agent (88 to 96%): (3 to 10%): (1 to 2%) to obtain an active material powder;
[0048] (3) Taking the total mass of the solid components in the silicon-carbon negative electrode slurry as 100%, weigh 2-4% of the polyacrylic acid binder and set it aside; then add 20-40% of the standby polyacrylic acid binder, 20-50% of the sodium carboxymethyl cellulose solution in step (1) and a solvent to the active material powder, perform a fourth stirring for 10-30 minutes at a revolution speed of 10-15 rpm, and then perform a fifth stirring for 60-90 minutes at a revolution speed of 25-35 rpm and a dispersion speed of 2000-3500 rpm to obtain an intermediate slurry;
[0049] (4) Add 20-40% of the reserved polyacrylic acid binder in step (3) to the intermediate slurry, and perform a sixth stirring for 10-30 minutes at a revolution speed of 10-15 rpm and a dispersion speed of 200-500 rpm, and then perform a seventh stirring for 60-120 minutes at a revolution speed of 25-35 rpm and a dispersion speed of 2000-3500 rpm; then add the remaining sodium carboxymethyl cellulose solution, polyacrylic acid binder and solvent, and perform an eighth stirring for 10-30 minutes at a revolution speed of 10-15 rpm and a dispersion speed of 400-1000 rpm, and then perform a ninth stirring for 90-120 minutes at a revolution speed of 25-35 rpm and a dispersion speed of 2000-3500 rpm, so as to obtain a silicon-carbon negative electrode slurry with a viscosity of 3000-6000 mPa·s.
[0050] In a second aspect, the present invention provides a silicon-carbon negative electrode slurry, which is prepared by the preparation method described in the first aspect.
[0051] In a third aspect, the present invention provides a silicon-carbon negative electrode sheet, which is obtained by coating the silicon-carbon negative electrode slurry described in the second aspect on the surface of the negative electrode current collector.
[0052] In a fourth aspect, the present invention further provides a lithium-ion battery, wherein the lithium-ion battery comprises the silicon-carbon negative electrode sheet as described in the third aspect.
[0053] Compared with the prior art, the present invention has the following beneficial effects:
[0054] The method for preparing silicon-carbon negative electrode slurry provided by the present invention effectively reduces the viscosity of the silicon-carbon negative electrode slurry during preparation by adding a specific sodium carboxymethyl cellulose solution and a polyacrylic acid binder, reduces wear on equipment, can ensure that the viscosity, solid content and fineness of the slurry are within the standard range, and suppresses the volume expansion phenomenon of CVD silicon-carbon during use. When applied to lithium-ion batteries, it shows excellent battery performance, and the preparation method is simple and suitable for large-scale application. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 This is a flow chart of the preparation method of the silicon-carbon negative electrode slurry in Example 1. DETAILED DESCRIPTION
[0056] The technical scheme of the present invention is further illustrated by specific examples below. Those skilled in the art should understand that the examples are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0057] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.
[0058] Example 1
[0059] This embodiment provides a lithium ion battery negative electrode slurry, such as Figure 1 As shown, it is obtained by the following preparation method:
[0060] (1) Preparation of sodium carboxymethyl cellulose solution (CMC solution)
[0061] Taking the total mass of the solid components of the silicon-carbon negative electrode slurry as 100%, weigh 1.5% of sodium carboxymethyl cellulose powder (CMC) by mass, and mix the sodium carboxymethyl cellulose powder with water in a double planetary mixer at a mass ratio of 1.5%:98.5%, and then perform the first stirring for 50 minutes at a revolution speed of 17rpm and a dispersion speed of 800rpm. After the first stirring is completed, scrape the pot wall and the stirring paddle, then turn on the vacuum, turn on the circulating water, and perform the second stirring for 400 minutes at a revolution speed of 25rpm and a dispersion speed of 1500rpm. After the second stirring is completed, test its viscosity and control it at 10,000 to 20,000 mPa·s;
[0062] (2) Mixed negative electrode active materials
[0063] The prepared negative electrode active material graphite, CVD silicon carbon powder and conductive carbon black (SP) were added to a double planetary mixer in a mass ratio of 92%:6%:2% for mixing, and a third stirring was performed for 50 min at a revolution speed of 20 rpm and a dispersion speed of 700 rpm to obtain a uniformly mixed active material powder;
[0064] (3) Kneading of negative electrode active material
[0065] Taking the total mass of the solid components in the silicon-carbon negative electrode slurry as 100%, weigh 3% of the polyacrylic acid binder (PAA) by mass and set aside; add 30% of the prepared sodium carboxymethyl cellulose solution, 30% of the total polyacrylic acid binder and water to the above-obtained uniformly mixed active material powder, first perform the fourth stirring at a revolution speed of 12 rpm for 20 min, and then perform the fifth stirring at a revolution speed of 30 rpm and a dispersion speed of 3000 rpm for 80 min;
[0066] (4) Forming silicon-carbon negative electrode slurry
[0067] 30% of the total polyacrylic acid binder and water were added to the above intermediate slurry, followed by a sixth stirring at a revolution speed of 13 rpm and a dispersion speed of 300 rpm for 20 minutes, and a seventh stirring at a revolution speed of 30 rpm and a dispersion speed of 3000 rpm for 90 minutes. After the seventh stirring, the remaining polyacrylic acid binder, the remaining sodium carboxymethyl cellulose solvent and water were added, followed by a ninth stirring at a revolution speed of 13 rpm and a dispersion speed of 700 rpm for 20 minutes, and a ninth stirring at a revolution speed of 30 rpm and a dispersion speed of 3000 rpm for 100 minutes. The viscosity was measured to be approximately 3000 to 6000 mPa·s.
[0068] Example 2
[0069] This embodiment provides a lithium ion battery negative electrode slurry, which is obtained by the following preparation method:
[0070] (1) Preparation of sodium carboxymethyl cellulose solution
[0071] Taking the total mass of the solid components of the silicon-carbon negative electrode slurry as 100%, weigh 0.5% of sodium carboxymethyl cellulose powder, and mix the sodium carboxymethyl cellulose powder with water in a double planetary mixer at a mass ratio of 2%:98%, and then perform the first stirring for 30 minutes at a revolution speed of 15rpm and a dispersion speed of 500rpm. After the stirring is completed, scrape the pot wall and the stirring paddle, then turn on the vacuum, turn on the circulating water, and perform the second stirring for 300 minutes at a revolution speed of 20rpm and a dispersion speed of 1000rpm. After the stirring is completed, test its viscosity and control it at 10000-20000mPa·s;
[0072] (2) Mixed negative electrode active materials
[0073] The prepared negative electrode active material graphite, CVD silicon carbon powder and SP were added to a double planetary mixer in a mass ratio of 90%:9%:1% for mixing, and the third stirring was performed for 30 minutes at a revolution speed of 15 rpm and a dispersion speed of 200 rpm to obtain a uniformly mixed active material powder;
[0074] (3) Kneading of negative electrode active material
[0075] Taking the total mass of the solid components in the silicon-carbon negative electrode slurry as 100%, weigh 2% of the polyacrylic acid binder by mass and set aside; add 20% of the sodium carboxymethyl cellulose solution prepared in step (1), 20% of the total polyacrylic acid binder and water to the above-obtained uniformly mixed active material powder, first perform a fourth stirring at a revolution speed of 10 rpm for 10 min, and then perform a fifth stirring at a revolution speed of 25 rpm and a dispersion speed of 2000 rpm for 60 min;
[0076] (4) Forming silicon-carbon negative electrode slurry
[0077] 40% of the total polyacrylic acid binder and water were added to the intermediate slurry, followed by a sixth stirring at a revolution speed of 15 rpm and a dispersion speed of 500 rpm for 30 minutes, and a seventh stirring at a revolution speed of 35 rpm and a dispersion speed of 3500 rpm for 120 minutes. After the seventh stirring, the remaining polyacrylic acid binder, the remaining sodium carboxymethyl cellulose solvent and water were added, followed by an eighth stirring at a revolution speed of 15 rpm and a dispersion speed of 1000 rpm for 30 minutes, and a ninth stirring at a revolution speed of 35 rpm and a dispersion speed of 3500 rpm for 120 minutes. The viscosity was measured to be about 3000 to 6000 mPa·s.
[0078] Example 3
[0079] This embodiment provides a lithium ion battery negative electrode slurry, which is obtained by the following preparation method:
[0080] (1) Preparation of sodium carboxymethyl cellulose solution
[0081] Taking the total mass of the solid components of the silicon-carbon negative electrode slurry as 100%, weigh 2% of sodium carboxymethyl cellulose powder, and mix it in a double planetary mixer at a mass ratio of 1%:99% of sodium carboxymethyl cellulose powder and water, and then perform the first stirring for 60 minutes at a revolution speed of 18rpm and a dispersion speed of 1000rpm. After the stirring is completed, scrape the pot wall and the stirring paddle, then turn on the vacuum, turn on the circulating water, and perform the second stirring for 500 minutes at a revolution speed of 30rpm and a dispersion speed of 2000rpm. After the stirring is completed, test its viscosity and control it at 10000-20000mPa·s;
[0082] (2) Mixed negative electrode active materials
[0083] The prepared negative electrode active material graphite, CVD silicon carbon powder and SP were added to a double planetary mixer in a mass ratio of 96%:3%:1% for mixing, and the third stirring was performed for 60 min at a revolution speed of 25 rpm and a dispersion speed of 1000 rpm to obtain a uniformly mixed active material powder;
[0084] (3) Kneading of negative electrode active material
[0085] Taking the total mass of the solid components in the silicon-carbon negative electrode slurry as 100%, weigh 4% of the polyacrylic acid binder by mass and set aside; add 50% sodium carboxymethyl cellulose solution by mass, 40% of the total polyacrylic acid binder and water to the above-obtained uniformly mixed active material powder, first perform the fourth stirring at a revolution speed of 15 rpm for 30 min, and then perform the fifth stirring at a revolution speed of 35 rpm and a dispersion speed of 3500 rpm for 90 min;
[0086] (4) Forming silicon-carbon negative electrode slurry
[0087] 20% of the total polyacrylic acid binder and water were added to the intermediate slurry, followed by a sixth stirring at a revolution speed of 10 rpm and a dispersion speed of 200 rpm for 10 minutes, and a seventh stirring at a revolution speed of 25 rpm and a dispersion speed of 2000 rpm for 60 minutes. After the stirring was completed, the remaining polyacrylic acid binder, the remaining sodium carboxymethyl cellulose solvent and water were added, followed by an eighth stirring at a revolution speed of 10 rpm and a dispersion speed of 400 rpm for 10 minutes, and a ninth stirring at a revolution speed of 25 rpm and a dispersion speed of 2000 rpm for 90 minutes. The viscosity was measured to be about 3000 to 6000 mPa·s.
[0088] Example 4
[0089] The difference between this embodiment and embodiment 1 is that in step (1), 0.3% by weight of sodium carboxymethyl cellulose powder is weighed.
[0090] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0091] Example 5
[0092] The difference between this embodiment and embodiment 1 is that in step (1), 3% by weight of sodium carboxymethyl cellulose powder is weighed.
[0093] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0094] Example 6
[0095] The difference between this embodiment and embodiment 1 is that in step (3), 1% by weight of polyacrylic acid binder is weighed and set aside.
[0096] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0097] Example 7
[0098] The difference between this embodiment and embodiment 1 is that in step (3), 6% by weight of polyacrylic acid binder is weighed and set aside.
[0099] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0100] Example 8
[0101] The difference between this embodiment and embodiment 1 is that in step (3), 10% of the sodium carboxymethyl cellulose solution is added to the uniformly mixed active substance powder obtained.
[0102] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0103] Example 9
[0104] The difference between this embodiment and embodiment 1 is that in step (3), 60% of the sodium carboxymethyl cellulose solution is added to the uniformly mixed active substance powder obtained.
[0105] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0106] Example 10
[0107] The difference between this embodiment and embodiment 1 is that in step (3), 10% of the total polyacrylic acid binder is added to the obtained uniformly mixed active material powder.
[0108] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0109] Embodiment 11
[0110] The difference between this embodiment and embodiment 1 is that in step (3), 50% of the total polyacrylic acid binder is added to the obtained uniformly mixed active material powder.
[0111] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0112] Example 12
[0113] The difference between this embodiment and embodiment 1 is that in step (4), 10% of the total polyacrylic acid binder is added to the slurry obtained in step (3).
[0114] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0115] Embodiment 13
[0116] The difference between this embodiment and embodiment 1 is that in step (4), 50% of the total polyacrylic acid binder is added to the slurry obtained in step (3).
[0117] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0118] Embodiment 14
[0119] The difference between this embodiment and embodiment 1 is that in step (1), stirring is performed at an orbital speed of 18 rpm and a dispersion speed of 1000 rpm for 60 min, and no subsequent stirring is performed.
[0120] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0121] Comparative Example 1
[0122] The difference between this comparative example and Example 1 is that all the prepared sodium carboxymethyl cellulose solution, all the polyacrylic acid binder and water are added to the intermediate slurry obtained in step (2) at one time, and the mixture is first stirred at an orbital speed of 12 rpm for 60 min, and then stirred at an orbital speed of 30 rpm and a dispersion speed of 3000 rpm for 270 min.
[0123] The rest of the preparation methods and parameters were consistent with those in Example 1.
[0124] Comparative Example 2
[0125] The difference between this comparative example and Example 1 is that no polyacrylic acid binder is added in step (3), the sixth stirring and the seventh stirring are not performed in step (4), and all the polyacrylic acid binder is added in the eighth stirring.
[0126] Other preparation methods and parameters were consistent with those in Example 1.
[0127] Comparative Example 3
[0128] The difference between this comparative example and Example 1 is that the sixth stirring and the seventh stirring are not performed in step (4).
[0129] Other preparation methods and parameters were consistent with those in Example 1.
[0130] Performance Testing
[0131] The silicon-carbon negative electrode slurry prepared in Examples 1 to 14 and Comparative Examples 1 to 3 was coated on the surface of copper foil to obtain a silicon-carbon negative electrode sheet, and then its powder loss rate and peeling force were tested; the silicon-carbon negative electrode sheet and the positive electrode sheet were prepared into a lithium-ion battery equipped with a silicon-carbon negative electrode by winding, packaging, liquid injection, formation, capacity division, aging, and sorting, and then the prepared lithium-ion battery was tested for initial discharge specific capacity, first week coulomb efficiency, and cycle capacity retention rate using a Xinwei test cabinet at 20°C. The test results are shown in Table 1:
[0132] Table 1
[0133]
[0134]
[0135] From the data comparison of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be seen that the silicon-carbon negative electrode prepared by the method for preparing the silicon-carbon negative electrode slurry provided by the present invention has a greatly reduced powder loss rate; when applied to lithium-ion batteries, it shows a higher first-week efficiency, and after 100 cycles, it has a higher capacity retention rate. This shows that the method for preparing the silicon-carbon negative electrode slurry provided by the present invention, through the specific order of adding sodium carboxymethyl cellulose solution and polyacrylic acid binder, can not only ensure that the viscosity, solid content and fineness of the slurry are within the standard range, reduce wear on the equipment, but also effectively inhibit the volume expansion phenomenon of CVD silicon-carbon during use, thereby improving the capacity retention rate of the lithium-ion battery and improving the overall performance of the battery.
[0136] From the data comparison of Examples 4 to 7 and Example 1 in Table 1, it can be seen that changing the amount of sodium carboxymethyl cellulose and polyacrylic acid binder added in the preparation of the entire silicon-carbon negative electrode slurry will affect the powder loss rate and peeling force of the negative electrode sheet, affect the volume expansion degree of CVD silicon-carbon during use, and thus affect the comprehensive performance of the battery; in practical applications, different mass fractions of sodium carboxymethyl cellulose and polyacrylic acid binder can be selected based on the powder loss rate, peeling force and electrochemical performance of the negative electrode slurry. Taking the total mass of the solid components of the silicon-carbon negative electrode slurry as 100%, when the mass proportion of sodium carboxymethyl cellulose is 0.5-2% and the mass proportion of the polyacrylic acid binder is 2-4%, it is more conducive to obtaining a negative electrode slurry with excellent comprehensive performance.
[0137] From the data comparison of Examples 8 to 13 and Example 1 in Table 1, it can be seen that changing the amount of polyacrylic acid binder and / or sodium carboxymethyl cellulose added in different mixing stages will also affect the physical and chemical properties of the silicon-carbon negative electrode sheet and the battery performance. Taking the total mass of all polyacrylic acid binders and all sodium carboxymethyl cellulose solutions as 100%, when the mass proportion of the first part of the polyacrylic acid binder is 20-40%, the mass proportion of the first part of the sodium carboxymethyl cellulose solution is 20-50%, and the mass proportion of the second part of the polyacrylic acid binder is 20-40%, it is more conducive to the uniform dispersion of the silicon-carbon negative electrode slurry, thereby being more conducive to the improvement of the comprehensive performance of the negative electrode slurry.
[0138] From the comparison of the data of Example 14 and Example 1 in Table 1, it can be seen that during the mixing process of the sodium carboxymethyl cellulose solution, by adding a second stirring, the mixing effect of the sodium carboxymethyl cellulose solution can be further improved, thereby obtaining a silicon-carbon negative electrode slurry with better comprehensive performance.
[0139] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a silicon-carbon negative electrode slurry, characterized in that: The preparation method comprises: (1) mixing sodium carboxymethyl cellulose powder and a solvent to obtain a sodium carboxymethyl cellulose solution; (2) performing a second mixing of the negative electrode active material and the conductive agent to obtain active material powder; (3) adding a portion of the sodium carboxymethyl cellulose solution, the first portion of the polyacrylic acid binder, and the solvent to the active substance powder for a third mixing to obtain an intermediate slurry; (4) adding the second part of the polyacrylic acid binder to the intermediate slurry for a fourth mixing, and then adding the remaining sodium carboxymethyl cellulose solution, the third part of the polyacrylic acid binder and the solvent for a fifth mixing; The negative electrode active material includes CVD silicon carbon.
2. The method for preparing the silicon-carbon negative electrode slurry according to claim 1, characterized in that: Taking the total mass of the solid components in the silicon-carbon negative electrode slurry as 100%, in step (1), the mass proportion of the sodium carboxymethyl cellulose powder is 0.5-2%; Preferably, in step (1), the mass ratio of the sodium carboxymethyl cellulose powder to the solvent is (1-2%):(98-99%); Preferably, the first mixing process is: a first stirring for 30 to 60 minutes at a revolution speed of 15 to 18 rpm and a dispersion speed of 500 to 1000 rpm, and then a second stirring for 300 to 500 minutes at a revolution speed of 20 to 30 rpm and a dispersion speed of 1000 to 2000 rpm; Preferably, the viscosity of the sodium carboxymethyl cellulose solution is 10000-20000 mPa·s; Preferably, after the first stirring is completed, the pot wall and the stirring paddle are scraped, the vacuum is turned on, and the circulating water is turned on.
3. The method for preparing the silicon-carbon negative electrode slurry according to claim 1 or 2, characterized in that: The negative electrode active material also includes graphite; Preferably, the mass ratio of the graphite, CVD silicon carbon powder and conductive agent is (88-96%): (3-10%): (1-2%); Preferably, the second mixing process is: performing a third stirring for 30 to 60 minutes at a revolution speed of 15 to 25 rpm and a dispersion speed of 200 to 1000 rpm.
4. The method for preparing the silicon-carbon negative electrode slurry according to any one of claims 1 to 3, characterized in that: Taking the total mass of the solid components in the silicon-carbon negative electrode slurry as 100%, the total mass of the first part, the second part and the third part of the polyacrylic acid binder accounts for 2-4%; Preferably, based on the total mass of the first part, the second part and the third part of the polyacrylic acid binder being 100%, the mass of the first part of the polyacrylic acid binder in step (3) accounts for 20-40%; Preferably, based on the mass of the sodium carboxymethyl cellulose solution in step (1) being 100%, the mass of the first part of the sodium carboxymethyl cellulose solution in step (3) accounts for 20 to 50%; Preferably, the third mixing process is: a fourth stirring for 10 to 30 minutes at an orbital speed of 10 to 15 rpm, and then a fifth stirring for 60 to 90 minutes at an orbital speed of 25 to 35 rpm and a dispersion speed of 2000 to 3500 rpm.
5. The method for preparing the silicon-carbon negative electrode slurry according to any one of claims 1 to 4, characterized in that: Taking the total mass of the first part, the second part and the third part of the polyacrylic acid binder as 100%, in the fourth mixing of step (4), the mass of the second part of the polyacrylic acid binder accounts for 20-40%; Preferably, the fourth mixing process is: a sixth stirring for 10 to 30 minutes at an orbital speed of 10 to 15 rpm and a dispersion speed of 200 to 500 rpm, and then a seventh stirring for 60 to 120 minutes at an orbital speed of 25 to 35 rpm and a dispersion speed of 2000 to 3500 rpm.
6. The method for preparing the silicon-carbon negative electrode slurry according to claim 1, characterized in that: The fifth mixing process of step (4) is: an eighth stirring for 10 to 30 minutes at a revolution speed of 10 to 15 rpm and a dispersion speed of 400 to 1000 rpm, and then a ninth stirring for 90 to 120 minutes at a revolution speed of 25 to 35 rpm and a dispersion speed of 2000 to 3500 rpm; Preferably, the viscosity of the silicon-carbon negative electrode slurry is 3000-6000 mPa·s.
7. The method for preparing the silicon-carbon negative electrode slurry according to claim 1, characterized in that: The preparation method comprises: (1) Taking the total mass of the solid components of the silicon-carbon negative electrode slurry as 100%, weigh 0.5-2% of sodium carboxymethyl cellulose powder by mass, and prepare a sodium carboxymethyl cellulose solution according to the mass ratio of sodium carboxymethyl cellulose powder to solvent of (1-2%): (98-99%), and perform a first stirring for 30-60 minutes at a revolution speed of 15-18 rpm and a dispersion speed of 500-1000 rpm. After the first stirring is completed, scrape the pot wall and the stirring paddle, turn on the vacuum, turn on the circulating water, and perform a second stirring for 300-500 minutes at a revolution speed of 20-30 rpm and a dispersion speed of 1000-2000 rpm, so as to obtain a sodium carboxymethyl cellulose solution with a viscosity of 10000-20000 mPa·s; (2) performing a third stirring for 30 to 60 minutes at a revolution speed of 15 to 25 rpm and a dispersion speed of 200 to 1000 rpm according to a mass ratio of graphite, CVD silicon carbon powder and conductive agent (88 to 96%): (3 to 10%): (1 to 2%) to obtain an active material powder; (3) Taking the total mass of the solid components in the silicon-carbon negative electrode slurry as 100%, weigh 2-4% of the polyacrylic acid binder and set it aside; then add 20-40% of the standby polyacrylic acid binder, 20-50% of the sodium carboxymethyl cellulose solution in step (1) and a solvent to the active material powder, perform a fourth stirring for 10-30 minutes at a revolution speed of 10-15 rpm, and then perform a fifth stirring for 60-90 minutes at a revolution speed of 25-35 rpm and a dispersion speed of 2000-3500 rpm to obtain an intermediate slurry; (4) Add 20-40% of the reserved polyacrylic acid binder in step (3) to the intermediate slurry, and perform a sixth stirring for 10-30 minutes at a revolution speed of 10-15 rpm and a dispersion speed of 200-500 rpm, and then perform a seventh stirring for 60-120 minutes at a revolution speed of 25-35 rpm and a dispersion speed of 2000-3500 rpm; then add the remaining sodium carboxymethyl cellulose solution, polyacrylic acid binder and solvent, and perform an eighth stirring for 10-30 minutes at a revolution speed of 10-15 rpm and a dispersion speed of 400-1000 rpm, and finally perform a ninth stirring for 90-120 minutes at a revolution speed of 25-35 rpm and a dispersion speed of 2000-3500 rpm, so as to obtain a silicon-carbon negative electrode slurry with a viscosity of 3000-6000 mPa·s.
8. A silicon-carbon negative electrode slurry, characterized in that: The silicon-carbon negative electrode slurry is prepared by the preparation method according to any one of claims 1 to 7.
9. A silicon-carbon negative electrode sheet, characterized in that: The silicon-carbon negative electrode sheet is obtained by coating the silicon-carbon negative electrode slurry described in claim 8 on the surface of the negative electrode current collector.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the silicon-carbon negative electrode sheet as claimed in claim 9.
Citation Information
Patent Citations
Silicon-carbon composite anode for lithium-ion batteries
CN107408669A
Silicon-based negative electrode slurry, preparation method thereof and negative electrode plate
CN116230849A
Multi-dimensional hydrogen bond conductive adhesive synthesized from natural polymer product and preparation method and application of multi-dimensional hydrogen bond conductive adhesive
CN119208611A
Methods for producing binder-coated conductor-speckled active battery material agglomerations for electrodes
US11978908B1
Cited By
Secondary battery and preparation method thereof, energy storage device and electric equipment
CN119994215A
Secondary battery, method for preparing same, energy storage device, and electrical equipment
CN119994215B